Building battery energy storage design - Htun, Pyae Phyo (2019)
Sources of electricity generation are constantly evolving from coal, natural gases, hydro to clean and renewable energy such as solar energy and wind energy with several emerging technologies still under research. In this 21st century, the needs for the clean and renewable energies have never been in demand before due to climate changes and global warming. In Singapore context, solar is the most accessible renewable energy due to its geographical location near to the equator. Although renewable energies are good for the environment, however, the supply of such renewable energy is not consistent and constant. It depends greatly on weather, time and season. As such, back-up energy storage solution is usually applied for a more reliable energy supply system. Excess generated energy will be charged and stored in the storage unit and utilize when there is a deficit. The aim of this project is to design the appropriate energy storage system for a selection of different building types running with off-grid solar PV system in Singapore.